Dynamics of the sensitivity of N. gonorrhoeae strains found in the territory of the Russian Federation in 2010-2013 to antimicrobial drugs used for the treatment of gonococcal infection - V. S. Solomka (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. To study the sensitivity of N. gonorrhoeae strains found in the territory of the Russian Federation in 2010- 2013 to antimicrobial drugs. Materials and methods. During the monitoring of antibiotic resistance of N. gonorrhoeae in 2010-2013, phenotypic properties of N. gonorrhoeae strains to antimicrobial drugs (penicillin, tetracycline, ciprofloxacin, spectinomycin, azithromycin and ceftriaxone) were examined by the agar serial dilution technique. As many as 1,305 viable N. gonorrhoeae strains from different regions of the russian Federation were examined. The results were evaluated according to the criteria such as CLSI (Clinical and Laboratory Standards Institution) and EUCAST (European Committee for Antimicrobial Susceptibility Testing). The results were processed by using the WHONET software, version 5.4. Results. According to the results of a study of N. gonorrhoeae antibiotic resistance, N. gonorrhoeae is highly resistant to penicillin (in 2010 - 72.4%, in 2011 - 50.6%, in 2012 - 51.2%, in 2013 - 49.3%), to tetracycline (in 2010 - 68.5%, in 2011 - 55%, in 2012 - 61.9%, in 2013 - 49.3%) and ciprofloxacin (in 2010 - 56.2%, in 2011 - 37.1%, in 2012 - 35%, in 2013 - 24.6%) for the entire observation period without any substantial trend towards its reduction. During studies of the resistance of the gonococcal infection pathogen to spectinomycin, the share of non-sensitive strains to the antibiotic reduced from 16.7% in 2010 to 0.7% in 2013. A slight reduction in the share of non-sensitive N. gonorrhoeae strains to azithromycin was also observed (in 2010 - 15.3%, in 2011 - 25.3%, in 2012 - 17.5%, in 2013 - 9.9%) yet these data substantially exceed the level recommended by the WHO for prescribing an antimicrobial therapy. A high level of N. gonorrhoeae sensitivity to ceftriaxone (100%) was revealed in 2010-2013. Conclusions. According to the analysis of resistance of N. gonorrhoeae strains to antimicrobial drugs found in the territory of the russian Federation in 2010-2013, there is a trend towards the reduction in the number of non-sensitive N. gonorrhoeae strains to penicillin, tetracycline, ciprofloxacin, spectinomycin and azithromycin, which can confirm the efficacy of the Neisseria gonorrhoeae antibiotic resistance monitoring measures taken by State research Center of Dermatovenereology and Cosmetology since 2002.